Respuesta :
we have that
Log3 a/3
Rewrite log3(a/3) using the change of base formula
we know that
The change of base rule can be used if a and b are greater than 0 and not equal to 1, and x is greater than 0.
so
loga(x)=logb(x)/logb(a)
Substitute in values for the variables in the change of base formula
in this problem
b=10
a=3
x=a/3
log3(a/3)=[log (a/3)]/[log (3)]
the answer is
[log (a/3)]/[log (3)]
Log3 a/3
Rewrite log3(a/3) using the change of base formula
we know that
The change of base rule can be used if a and b are greater than 0 and not equal to 1, and x is greater than 0.
so
loga(x)=logb(x)/logb(a)
Substitute in values for the variables in the change of base formula
in this problem
b=10
a=3
x=a/3
log3(a/3)=[log (a/3)]/[log (3)]
the answer is
[log (a/3)]/[log (3)]